The other as a mirror for democracy: the question of national identity in European perspective - Astrouskaya, Tatsiana (Видавництво Львівської політехніки, 2011)
Article is devoted to the problem of national identity in modern western European society. From the author’s point of view, the relation to immigrant and maintenance of his/her rights is the important criterion of democratization and can be helpful to the analysis of identity. The author examines possible decisions from the perspective of immigration legislation improvement and the perspective of different educational strategies application through the prism of theoretical implications of modern social philosophers – Z. Bauman and S. Benhabib.
Іншість, як дзеркало для демократії: питання національної ідентичності у європейській перспективі
Keywords: national identity; the other; migration; democracy; culture